Pengaruh Spesialisasi Auditor, Komite Audit, Financial Distress Dan Audit Capacity Stress Terhadap Kualitas Audit - Hermania Putri Dwi Yulianty; Adam Zakaria; Hera Khairunnisa (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This research aims to analyze the influence of auditor specialization, audit committee, financial distress,and audit capacity stress of 38 consumer goods industry listed companies on Indonesia Stock Exchange in 2021-2023. The data used is secondary data by downloading data from the official website of the Indonesian stock exchange and the official website of the related company. The data collection method uses a purposive sampling method based on predetermined criteria. Logistic regression techniques were used for the analysis method in this research. The result of the hypothesis test show that auditor specialization and audit capacity stress had effect on audit quality. In contrast, audit committee and financial distress are had no effect on audit quality.